Neurolymphomatosis of the lumbosacral plexus and its branches: case series and literature review - Bourque, Pierre R; Sampaio, Marcos L; Warman-Chardon, Jodi; Samaan, Sam; Torres, Carlos (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Neurolymphomatosis (NL) is a direct process of invasion of peripheral nerves by lymphoma. It occurs in roughly 5% of patients with lymphoma and represents a particularly difficult diagnostic dilemma when it is the presenting focal manifestation of occult lymphoma. Case presentation We present 3 examples of invasion of the lumbosacral plexus and its branches. These cases demonstrate a protean clinical picture with regards to the time relationship to the clinical course of lymphoma and the neuroanatomical extent of lumbosacral plexus invasion. We demonstrate the complementary role of different imaging modalities. A review of the literature summarizes 23 reports where lumbosacral plexus invasion was the index manifestation, at the time of first diagnosis or recurrence of lymphoma. This series confirms the strong preponderance of B-cell type (92%). There is a marked predilection for involvement of the sciatic nerve (74%), either focally or in a longitudinally extensive fashion, from the ischium to the popliteal fossa. There can also be restricted and discrete involvement of tibial and fibular branches. In recent years, ultrasound and CT have been given a more limited role, as screening tools or as a guide for biopsy. MRI neurography and PET-CT have become leading diagnostic modalities for diagnosis, staging and assessment of treatment response. Conclusion The diagnosis of NL may be challenging, and it was once only reached at autopsy. Improved diagnostic imaging of focal or even asymptomatic disease offers new hope for earlier diagnosis and successful targeted therapy.